EVOLUTION OF THE RADON REGULATION IN DOMESTIC STANDARDIZATION - A. T. Gubin; V. A. Sakovich; Yu. A. Soloview (Радиационная гигиена)
Briefly considered history of the  development and present status of the normative-methodical basis for the limitation of man-made and natural radon influence on personnel and population. It is analyzed the transfer factors from radon radiometric values to effective dose, corresponding to various versions of RSS and normative-methodical documents for limitation of the irradiation from natural sources. It is formulated proposals to the  new RSS editing in a part of the standardization of  radon.